Immunoreactive insulin in diabetes mellitus patient sera detected by ultrasensitive ELISA with thio-NAD cycling. (December 2015) - Ito, Etsuro; Kaneda, Mugiho; Kodama, Hiromi; Morikawa, Mika; Tai, Momoko; Aoki, Kana; Watabe, Satoshi; Nakaishi, Kazunari; Hashida, Seiichi; Tada, Satoshi; Kuroda, Noriyuki; Imachi, Hitomi; et al.
To minimize patient suffering, the smallest possible volume of blood should be collected for diagnosis and disease monitoring. When estimating insulin secretion capacity and resistance to insulin in diabetes mellitus (DM), increasing insulin assay immunosensitivity would reduce the blood sample volume required for testing. Here we present an ultrasensitive ELISA coupled with thio-NAD cycling to measure immunoreactive insulin in blood serum. Only 5 µL of serum was required for testing, with a limit of detection (LOD) for the assay of 10 −16 moles/assay. Additional recovery tests confirmed this method can detect insulin in sera. Comparisons between a commercially available immunoreactive insulin kit and our ultrasensitive ELISA using the same commercially available reference demonstrated good data correlation, providing further evidence of assay accuracy. Together, these results demonstrate our ultrasensitive ELISA could be a powerful tool in the diagnosis and treatment of not only DM but also many other diseases in the future.